An old activity in the cytochrome P450 superfamily (CYP51) and a new story of drugs and resistance. (May 2001) - Kelly, S. L.; Lamb, D. C.; Cannieux, M.; Greetham, D.; Jackson, C. J.; Marczylo, T.; Ugochukwu, C.; Kelly, D. E.
Abstract : Cytochrome P450 51 (CYP51) is sterol 14α-demethylase, known also as Ergllp in yeast. First studied in yeast, where it is one of three CYPs in the genome, it has subsequently gained attention as the only CYP found so far in different kingdoms of life. As such it is central to considerations of CYP evolution. Recent use of CYP51-inhibiting antifungal drugs, such as fluconazole, has also been associated with dramatic CYP51 evolution to numerous resistant forms in fungal pathogens. CYP51 has also been discovered in mycobacteria where antifungal azoles have effect and might be of value against tuberculosis. Evolutionary and therapeutic aspects of CYP51 studies are discussed.